Severe Phantom Leg Pain in an Amputee After Lumbar Plexus Block. Issue 5 (1st September 2003) - Martin, Gavin; Grant, Stuart A.; MacLeod, David B.; Breslin, Dara S.; Brewer, Randall P.
Abstract : Objectives: To describe the onset of phantom leg pain in an amputee with the performance of a lumbar plexus block and the subsequent alleviation after the performance of a sciatic nerve block. Case Report: A 72-year-old American Society of Anesthesiologists physical status III woman presented for left total hip arthroplasty. Her history was significant for a left below the knee amputation. Since the amputation she had suffered from intermittent phantom leg pain. A lumbar plexus block was performed for postoperative pain management. After the lumbar plexus block, the patient experienced severe pain radiating to the left phantom foot. Because of the severity of the phantom pain, a sciatic nerve block was performed. The phantom leg pain resolved within 5 minutes. The intraoperative care under general anesthesia was uneventful. After surgery the patient had continued blockade in both nerve distributions with excellent analgesia. Full recovery of the lumbar plexus and sciatic nerve function was present on the first postoperative day. Conclusion: The temporal relationship between the onset of the phantom leg pain and the lumbar plexus block suggests a causal relationship. In this case, it appears that ongoing peripheral input from the lumbar plexus may have been sufficient for the tonic inhibition of phantom pain in the sciatic distribution. The immediate reactivation of the phantom pain and its subsequent relief suggests dynamic processing of peripheral inputs by central neurons, which apparently is rapid and reversible in some cases of phantom pain.